PENGARUH MEDIA VIDEO TERHADAP KETERAMPILAN MENYIMAK TEKS BERITA SISWA KELAS VIII SMP NEGERI 4 KAHU - Nurfadilla; Muh Safar (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to (1) describe the listening skills of news texts before using video media in Class VIII students of SMP Negeri 4 Kahu; (2) Describe the listening skills of news texts after using video media in Class VIII students of SMP Negeri 4 Kahu; (3) prove the significant influence of the use of video media on the listening skills of Class VIII students of SMP Negeri 4 Kahu. The type of research used is quantitative research using a Pre-Experimental model. The design in this study uses one group pretest-posttest. The population in this study were all 70 Class VIII students of SMP Negeri 4 Kahu. The sampling technique was simple random sampling using 23 students from each Class VIII.The results of this study indicate that: 1) The listening skills of Class VIII students of SMP Negeri 4 Kahu before using video media were in the less skilled category with an average score of Class VIII A (65), Class VIII B (69), and Class VIII C (65); 2) The listening skills of Class VIII students in news texts after using video media are in the skilled category with an average score in Class VIII A of (86), Class VIII B of (81), and Class VIII C (81); 3) There is an effect of the use of video media on the listening skills of news texts in Class VIII students of SMP Negeri 4 Kahu, which shows that HO is rejected and H1 is accepted.